Col d'Olen, soil chemistry (extractable N-NO3) 2008-2019 - Michele Freppaz; Davide Viglietti (Zenodo, 2020)
Dataset provides information about soil temperature, soil C and N dynamics at different sites in the alpine tundra, along an elevational gradient from 2500 to 2900 m asl during the period 2005-2018. The soil was sampled in triplicate in each the sites and the N-NO3 concentration is measured in soil K2SO4 extracts. The ongoing studies aimed at investigating how the meteorological variables affect the biogeochemistry of seasonally snow covered areas, with a special focus on the effect of the snow cover duration on soil and water C and N dynamics during the growing season.